Rule-based fuzzy logic controller with adaptable reference - Khan, Sheroz; Adam, I; Alam, A. H. M. Zahirul; Islam, Md. Rafiqul; Khalifa, Othman Omran (World Academy of Science, Engineering and Technology (W A S E T), 2008)
This paper attempts to model and design a simple fuzzy logic controller with Variable Reference. The Variable Reference (VR) is featured as an adaptability element which is obtained from two known variables – desired system-input and actual system-output. A simple fuzzy rule-based technique is simulated to show how the actual system-input is gradually tuned in to a value that closely matches the desired input. The designed controller is implemented and verified on a simple heater which is controlled by PIC Microcontroller harnessed by a code developed in embedded C. The output response of the PIC-controlled heater is analyzed and compared to the performances by conventional fuzzy logic controllers. The novelty of this work lies in the fact that it gives better performance by using less number of rules compared to conventional fuzzy logic controllers.